Localization of Pulmonary Ground-Glass Opacities with Folate Receptor–Targeted Intraoperative Molecular Imaging - Predina, Jarrod D.; Newton, Andrew; Corbett, Christopher; Xia, Leilei; Sulyok, Lydia Frenzel; Shin, Michael; Deshpande, Charuhas; Litzky, Leslie; Barbosa, Eduardo; Low, Philip S.; Kucharczuk, John C.; Singhal, Sunil (Journal of thoracic oncology, 2018)
Intraoperative localization and resection of ill-defined pulmonary ground-glass opacities (GGOs) during minimally invasive pulmonary resection is technically challenging. Current preoperative techniques to facilitate localization of GGOs include microcoil and hook wire placement, both of which have logistic limitations, carry safety concerns, and do not help with margin assessment. In this clinical trial, we explored an alternative method involving near-infrared molecular imaging with a folate receptor–targeted agent, OTL38, to improve localization of GGOs and confirmation of resection margins. In a human trial, 20 subjects with pulmonary GGOs who were eligible for video-assisted thoracoscopic surgery (VATS) resection received 0.025 mg/kg of OTL38 before the resection. The primary objectives were to (1) determine whether use of OTL38 allows safe localization of GGOs and assessment of margins during VATS and (2) determine patient, radiographic, and histopathologic variables that predict the amount of fluorescence during near-infrared imaging. We observed no toxicity. Of the 21 GGOs, 20 accumulated OTL38 and displayed fluorescence upon in situ or back table evaluation. Intraoperatively, near-infrared imaging localized 15 of 21 lesions whereas VATS alone localized 10 of 21 (p = 0.05). The addition of molecular imaging affected care of nine of 21 subjects by improving intraoperative localization (n = 6) and identifying close margins (n = 3). This approach was most effective for subpleural lesions measuring less than 2 cm. For lesions deeper than 1.5 cm from the pleural surface, intraoperative localization using fluorescent feedback was limited. This approach provides a safe alternative for intraoperative localization of small, peripherally located pulmonary lesions. In contrast to alternative localization techniques, use of OTL38 also allows confirmation of adequate margins. Future studies will compare this approach to alternative localization techniques in a clinical trial.